Amicarbazone, a New Photosystem II Inhibitor - Dayan, Franck E.; Trindade, Maria L. B. [UNESP]; Velini, Edivaldo Domingues [UNESP] (Weed Sci Soc Amer, 2009)
Amicarbazone is a new triazolinone herbicide with a broad spectrum of weed control. The phenotypic responses of sensitive plants exposed to amicarbazone include chlorosis, Stunted growth, tissue necrosis, and death. Its efficacy as both a foliar- and root-applied herbicide suggests that absorption and translocation of this compound is very rapid. This new herbicide is a potent inhibitor of photosynthetic electron transport, inducing chlorophyll fluorescence and interrupting oxygen evolution ostensibly via binding to the Q(B) domain of photosystem II (PSII) in a manner similar to the triazines and the triazinones classes of herbicides. As a result, its efficacy is susceptible to the most common form of resistance to PSII inhibitors. Nonetheless, amicarbazone has a good selectivity profile and is a more potent herbicide than atrazine, which enables its use at lower rates than those of traditional photosynthetic inhibitors.
Keywords: Herbicide mode of action; photosynthesis; photosystem II; herbicide resistance